Desenvolvimento pessoal baseado em conhecimento como antecedente de ecossistemas de inovação social: análise em cidades do conhecimento - Nespolo, Daniele (My University, 2020)
The intersection between urban economy, innovation networks, technology platforms, services and their applications, collective intelligence and theories on innovation underlie innovation ecosystems. The promotion of innovation-driven ecosystems by social dimension allows exploring alternatives for the transformation of knowledge cities and the generation of social innovation. The objective of this study is to analyze how knowledge-based personal development implies the creation and development of social innovation ecosystems for the creation and development of cities of knowledge. In order to achieve this goal, the relations between capital system constructs, knowledge citizenship and personal knowledge-based development as antecedents for the creation and development of social innovation ecosystems will be analyzed. The mixed methods approach will be used, covering the results of quantitative and qualitative research in a complementary way, using the strategy of sequential explanatory research. The population defined for the present study will be composed of company leaders, leaders of educational institutions, municipal public authorities and undergraduate students of the courses of Social and Applied Sciences belonging to the cities of Bento Gonçalves (Brazil), Arequipa (Peru) and Monterrey (Mexico). As a result, this research evidenced that social interaction and the information citizens have regarding their own cities are related to social structures, which is base for social innovation ecosystems in the cities here studied. The results also reveal that the perception of the agents involved in the ecosystem of social innovation, on the dimensions implied in capital system, is related to the belief in social transformation caused by universities, public authorities, private companies and companies of the third sector's performance. Such results enabled the proposal of a theoretical model for creation and development ecosystems of social innovation anchored on the structure of local principles integrated into the capital system in knowledge cities.
A intersecção entre economia urbana, redes de inovação, plataformas de tecnologia, serviços e suas aplicações, inteligência coletiva e as próprias teorias da inovação fundamenta os ecossistemas de inovação. A promoção dos ecossistemas de inovação orientados pela dimensão social possibilita a exploração de alternativas para a transformação das cidades do conhecimento. O presente estudo tem por objetivo analisar como o desenvolvimento pessoal baseado no conhecimento implica no desenvolvimento de ecossistemas de inovação social em cidades do conhecimento. Para atingir este objetivo foram analisadas as relações entre os construtos sistema de capitais e desenvolvimento pessoal baseado no conhecimento como antecedentes para a criação e o desenvolvimento de ecossistemas de inovação social. Foi utilizada a abordagem dos métodos mistos, abrangendo os resultados de uma pesquisa quantitativa e qualitativa de maneira complementar, sendo utilizada a estratégia da pesquisa sequencial explanatória. A população definida para o presente estudo é composta de dirigentes de empresas, dirigentes de instituições de ensino, dirigentes de empresas do terceiro setor (ONGs), dirigentes do poder público municipal e estudantes de graduação dos cursos da área de Ciências Sociais e Aplicadas pertencentes às cidades de Bento Gonçalves (Brasil), Arequipa (Peru) e Monterrey (México). Como resultado desta pesquisa evidenciou-se que a interação social e a informação que os cidadãos têm de suas cidades, estão associadas à estrutura social que fundamenta o ecossistema de inovação social nas cidades estudadas. Os resultados revelam também que a percepção dos agentes envolvidos no ecossistema de inovação social, sobre as dimensões que subjazem o sistema de capitais, está associada à crença na transformação social provocada pela atuação de Universidades, Poder Público, empresas privadas e Empresas do terceiro setor. Tais resultados possibilitaram a proposição de um modelo teórico para a criação e o desenvolvimento de ecossistemas de inovação social ancorados na estrutura de valores locais integrados no sistema de capitais em cidades do conhecimento.
Keywords: Gestão do conhecimento; Tecnologia - Aspectos sociais; Sucesso; Desenvolvimento organizacional; Knowledge management; Technology Social aspects; Success; Organizational change